Performance of Bunaji Bulls Fed Pleurotus tuber regium Biodegraded Rice Offal Incorporated Diets: An Experimental Investigation - Wuanor, A. A.; Ayoade, J. A.; Yusuf , T. (Research Aspects in Agriculture and Veterinary Science Vol. 6, 2022)
This study was carried out with the objective of assessing the nutritive potential of rice offal biodegraded using Pleurotus tuber –regium (PTRO) as a feedstuff for growing Bunaji bulls. A total of twelve bulls with an average of 153 kg were used in the study, which lasted 90 days. In a Completely Randomized Design, the animals were divided into four (4) treatment groups (T1, T2, T3, and T4), each consisting of three (3) bulls. A basal diet of elephant grass was supplied ad libitum, as well as a concentrate containing the PTRO at 0.0 percent, 5.0 percent, 10.0 percent, and 15.0 percent at T1, T2, T3, and T4, respectively, offered at 3.0% body weight of the bulls, with drinking water available ad libitum. The experimental diet was formulated using palm kernel cake, brewers dried grain, Shea nut cake, maize offal, treated rice offal, untreated rice offal, bone ash and table salt. Findings for growth performance metrics reported at the completion of the research include average daily concentrate intake, average daily forage intake, average daily total feed intake, average daily water intake, average daily weight gain and feed conversion ratio for T1, T2, T3 and T4 were: 1.24, 1.05, 1.19 and 1.19 kg; 8.23, 8.53, 9.04 and 8.38 kg; 9.51, 9.59, 9.99 and 9.30 kg; 7.10, 6.16, 6.86 and 6.00 litres; 0.23, 0.2, 0.29 and 0.44 kg, and 43.35, 37.40, 34.27 and 20.73 respectively. Average daily concentrate intake and average daily water intake exhibited significant differences ((P<0.05)), whereas average daily forage intake, average daily total feed intake, average daily weight increase, and feed conversion ratio indicated no significant differences (P>0.05). Based on the findings, it was determined that diets containing Pleurotus tuber regium biodegraded rice offal were safe to give to feedlot Bunaji bulls. Keywords: Performance; Pleurotus- tuber-regium; biodegraded; rice- by product; feedlot; Bunaji bulls.